PROBLEMS OF USE OF PEDAGOGICAL AND INFORMATION TECHNOLOGIES IN THE PROCESS OF MODERN EDUCATION - G. Begmatova; B. Rakhmanov (International Journal of Innovations in Engineering Research and Technology, 2021)
The article discusses the problems of using information and pedagogical technologies in the learning process, the problems of pedagogical skill of teachers in the interactive process.